Treatment of nonmetastatic prostate cancer: a systematic review of interactive, personalized patient decision aids - Groeben, C.; Streuli, J. C.; Krones, T.; Keck, Bastian; Wirth, M. P.; Huber, J. (Urologe, 2014)
Patients with nonmetastatic prostate cancer face a complex treatment decision. To support them with personalized information, a variety of interactive computerized decision aids have been developed in Anglo-Saxon countries. Our goal was to identify relevant decision aids and investigate their didactic strengths and limitations.We included decision aids that derived individualized content from personal and clinical data provided by the patient. By conducting a systematic literature and internet research through November 2013 supplemented by expert interviews, we identified 10 decision aids of which 6 had been investigated scientifically. We compared their individual characteristics as well as the design and results of the evaluation studies.The decision aids present two to seven therapy choices, whereby radical prostatectomy and percutaneous radiotherapy are always included. Number and type of parameters provided by the patient also vary considerably. Two decision aids derive a therapeutic recommendation from the patient's input. Evaluation studies showed higher disease-related knowledge and greater confidence in the treatment decision after using one of six decision aids. Satisfaction with the decision aid was predominantly high.Currently personalized patient decision aids for treatment of nonmetastatic prostate cancer are only available in English. These tools can facilitate the shared decision making process for patients and physicians. Therefore, comparable decision aids should be developed in German.
EVALuna2:16297